Economic Empowerment Of Urban Women Through MSME Mentoring Based On Product Innovation And Digital Marketing In Kalirungkut Village, Surabaya - Imam Bahrozi; Pristiwiyanto; Atmari (LPPM, STAI Al-Azhar Menganti, 2025)
This Community Service Program (PKM) aims to strengthen the capacity, creativity, and economic independence of women engaged in Micro, Small, and Medium Enterprises (MSMEs) in Kalirungkut Village, Surabaya. The program was implemented through an intensive one-month mentoring initiative focusing on product innovation, packaging quality improvement, and the enhancement of simple digital marketing strategies through social media platforms. A participatory approach was employed, positioning participants as active contributors throughout all stages of the program, including needs assessment, training, practical implementation, and evaluation.The results indicate significant improvements in participants’ ability to develop more competitive product variations, enhance packaging design and quality, and utilize digital platforms as effective tools for promotion and marketing. Furthermore, the program increased participants’ self-confidence in managing their businesses, fostered collaborative networks among MSME actors, and improved their understanding of basic business management and financial administration. The positive impacts were reflected not only in the increased added value and marketability of products but also in the growth of entrepreneurial spirit and economic self-reliance among women in urban communities. Overall, the program contributed to strengthening women’s economic empowerment through the development of more innovative, adaptive, and sustainable MSMEs. In the future, similar mentoring models can be replicated and expanded to other MSME groups to support the creation of a more inclusive, competitive, and sustainable local economic ecosystem.